2022
DOI: 10.3390/healthcare10112196
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Type 2 Diabetes Mellitus in Patients with Acute Cholangitis: A Systematic Review of Current Literature

Abstract: Introduction: Type 2 diabetes mellitus (T2DM) has been associated with higher rates and poorer prognosis of infections, mainly due to poor glycemic control, reduced response of T-cells and neutrophils, and impaired migration, phagocytosis, and chemotaxis of leukocytes. However, the impact of T2DM on acute cholangitis (AC) has not been assessed so far. Thus, we aimed to explore this association by means of a systematic review of the literature. Methods: This systematic review was carried out based on the recomm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…The mean age for bacteriobilia associated with obstructive jaundice was between 61 and 75 years, representing (46%) of cases. This is in agreement with the results of other studies in the literature of reported cases of bacteriobilia in elderly patients above 70 years 11,29 . This is related to the altered immune response in the elderly patients.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The mean age for bacteriobilia associated with obstructive jaundice was between 61 and 75 years, representing (46%) of cases. This is in agreement with the results of other studies in the literature of reported cases of bacteriobilia in elderly patients above 70 years 11,29 . This is related to the altered immune response in the elderly patients.…”
Section: Discussionsupporting
confidence: 93%
“…Also, type-2 DM is associated with reduced response of T cells and neutrophils, impaired phagocytosis, intracellular killing, and leukocyte chemotaxis. 11 Our study showed that the positive results of bile culture is significantly associated with a confirmed history of ascending cholangitis in 34% of patients. These observations were in agreement with the study of Sharma et al who reported bacteriobilia was found more often in patients with a pervious history of cholangitis (47%) than those without (19%).…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…We see the successfully published articles of these collaborations as a transcript of our efforts. The manuscripts tackled topics in the fields of hematology and oncology, [17][18][19][20][21][22][23] ethics (e.g., diversity, equity and inclusion), [24][25][26][27] infectious diseases, 28,29 surgery, 30,31 pediatrics, 32 and physical and rehabilitation medicine. [33][34][35] We invite you to read them and encourage you to include students and early career scientists in your research projects.…”
Section: How To Make Editors and Scientists: An Ijms Initiativementioning
confidence: 99%